1996
DOI: 10.1074/jbc.271.17.9887
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of the Mouse apobec-1 Gene Abolishes Apolipoprotein B mRNA Editing and Eliminates Apolipoprotein B48

Abstract: A site-specific C to U editing reaction modifies nuclear apolipoprotein B100 (apoB100) mRNA, producing apolipoprotein B48 in the mammalian small intestine. This reaction is mediated by a multicomponent enzyme complex, which contains a catalytic subunit, Apobec-1. We have used gene targeting to disrupt mouse apobec-1 in order to establish its requisite importance in apoB mRNA editing and also, in view of its widespread tissue distribution in rodents, as a preliminary indication of other potential roles. Both he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
106
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 132 publications
(116 citation statements)
references
References 29 publications
(24 reference statements)
8
106
0
Order By: Relevance
“…As a positive control for this experiment, antisense oligonucleotide inhibition of apobec-1 expression demonstrated the anticipated elimination of editing activity (Fig. 9D, lanes 13-15), findings consistent with the results of gene targeting in mice (12,49,50). We have extended this paradigm with the demonstration that antisense oligonucleotide inhibition of ACF also results in loss of editing activity (Fig.…”
Section: Fig 6 Cugbp2 Is An Apob Rna-binding Proteinsupporting
confidence: 71%
“…As a positive control for this experiment, antisense oligonucleotide inhibition of apobec-1 expression demonstrated the anticipated elimination of editing activity (Fig. 9D, lanes 13-15), findings consistent with the results of gene targeting in mice (12,49,50). We have extended this paradigm with the demonstration that antisense oligonucleotide inhibition of ACF also results in loss of editing activity (Fig.…”
Section: Fig 6 Cugbp2 Is An Apob Rna-binding Proteinsupporting
confidence: 71%
“…The effects depended completely on the direction of the cross (Table 3), with Apobec1 acting in the female germ-lineage, and Dnd1 acting in the male germ-lineages. Loss of substantial numbers of single and double heterozygotes in the interaction test is remarkable, given that both ko/ko and Ter/Ter homozygotes are fully viable in separate crosses (36,42). Normal segregation also is found in mutant heterozygotes in separate crosses to wild-type mice (29; also see Table S3), showing that gametes are produced in normal ratios and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Test 2: Parental ko/+ heterozygosity. Because partial Apobec1 deficiency can lead to tissue-specific dysfunction (42,47), we asked whether parental ko/+ heterozygosity affected TGCT susceptibility (cross 2). For this test, we measured the frequency of affected ko/+ (test) wild type and (+/+) w (control) male offspring from reciprocal crosses between ko/+ heterozygotes and strain 129 wild-type (+/+) c homozygotes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that not all genes tested by RNAi have visible phenotypes when inhibited [27], and a cdd knock-out gene might fall into this category. In the mouse, deletion of apobec-1 did not provide any gross phenotype, except for the absence of apoB48 in the serum [31]. Recent studies on mammalian CDDs have revealed the existence of a family of related proteins [6], and in the C. elegans genome there is at least one other predicted protein that could potentially compensate for any phenotype obtained by RNAi with Ce-cdd-1 and -2.…”
Section: Discussionmentioning
confidence: 99%